PENYUSUNAN MEDIA PEMBELAJARAN BERBANTUAN KOMPUTER UNTUK PBL DAN KEEFEKTIFANNYA TERHADAP CTS PESERTA DIDIK SMA - Kurniawati, Atik; Suryadarma, I Gusti Putu (Jurnal Inovasi Pendidikan IPA, 2015)
This study aims to investigate: (1) the feasibility of computer-assisted learning media based problem based learning (PBL) on Environmental Pollution materials for high school students of class X, and (2) the effectiveness of instructional media for improving of critical thinking skill (CTS) learners class X SMA Negeri 5 Magelang. This research was adapted from the ADDIE model of development that includes analyze, design, develop, implement, and evaluate. Products validated by subject matter experts, media experts, educators of Biology, and peer reviewer. Subject of this study is tenth grade students of SMA Negeri 5 Magelang. Collecting data was using questionnaires, observation sheets, and test critical thinking skills. The media according to the validator and the students is classified to the category of good. Instructional media was improved to learners' critical thinking skills effectively, which demonstrated by the significant value of 0:00. This results showed that media computer-assisted learning based PBL is effective for improving of the critical thinking skills of learners.